Formulation and application of coatings based on banana skin flour in post-harvest conservation of fruit (Research, Society and Development, 2021)
The present study aimed to obtain and evaluate banana peel flours (Musa spp.) at different stages of maturation in the formulation of edible coatings to be applied to banana fruits, aiming at extending their shelf life and technological evaluation of the coatings produced. The experiment was divided into three stages: production and characterization of banana peel flour at different stages of maturation, where pH, titratable acidity (TA) and soluble solids (SS) were analyzed; film formulation with the incorporation of flours in different proportions, evaluating thickness, opacity, solubility and permeability to water vapor; and application of toppings on banana fruits and evaluating for mass loss, pH, TA, SS, ascorbic acid content, starch content and changes in the maturation stage during storage for 10 days at 25 ºC, using three repetitions of three fruits per treatment. Data were subjected to analysis of variance and regression, and means compared by Tukey test. The banana peel flour had higher acidity content when coming from fruits in more advanced stages of ripening. Uncoated fruits had ripening evidenced by the accelerated change in skin color. Edible films with banana peel flour showed acceptable characteristics and similar to other studies, where the formulations F3 and F4 had less thickness and permeability to water vapor than the other treatments, in addition to having demonstrated the use and potential of flours as a thickening agent.